Análisis de percepción en la comunidad universitaria de la denotación y connotación del logo de la Universidad Técnica de Babahoyo - Colcha Soto, Carmen (2023)
The logo of an educational institution plays a significant role in the construction of its identity and the way it is perceived both internally and externally. The Technical University of Babahoyo (UTB) is a higher education institution that has a logo that has been part of its institutional image for a considerable time. The perception that the university community has of this logo can influence their sense of belonging, identification with the institution and its reputation in the academic and social environment. The importance of this study lies in wanting to show the importance of understanding how the logo of the Technical University of Babahoyo is perceived and what meanings are attributed to it by the university community. The logo can have different implications in the management of institutional identity, in this way the communication and connection between the university and its members will be reinforced because we will thoroughly understand what meaning they wanted to give to the image that represents our institution. , can provide valuable information for future design and branding efforts of the institution.